Strength, Stability, and cis-Motifs of In silico Identified Phloem-Specific Promoters in Brassica juncea (L.) - Koramutla, Murali Krishna; Bhatt, Deepa; Negi, Manisha; Venkatachalam, Perumal; Jain, Pradeep K.; Bhattacharya, Ramcharan (Frontiers in Plant Science, 2016)
Abstract Aphids, a hemipteran group of insects pose a serious threat to many of the major crop species including Brassica oilseeds. Transgenic strategies for developing aphid-resistant plant types necessitate phloem-bound expression of the insecticidal genes. A few known phloem-specific promoters, in spite of tissue-specific activity fail to confer high level gene-expression. Here, we identified seven orthologues of phloem-specific promoters in B. juncea (Indian mustard), and experimentally validated their strength of expression in phloem exudates. Significant cis-motifs, globally occurring in phloem-specific promoters showed variable distribution frequencies in these putative phloem-specific promoters of B. juncea. In RT-qPCR based gene-expression study promoter of Glutamine synthetase 3A (GS3A) showed multifold higher activity compared to others, across the different growth stages of B. juncea plants. A statistical method employing four softwares was devised for rapidly analysing stability of the promoter-activities across the plant developmental stages. Different statistical softwares ranked these B. juncea promoters differently in terms of their stability in promoter-activity. Nevertheless, the consensus in output empirically suggested consistency in promoter-activity of the six B. juncea phloem- specific promoters including GS3A. The study identified suitable endogenous promoters for high level and consistent gene-expression in B. juncea phloem exudate. The study also demonstrated a rapid method of assessing species-specific strength and stability in expression of the endogenous promoters.